(untitled) (Journal of the College of Basic Education, 2025)
The press is one of the most important sources of modern and contemporary Iraqi history in detailing important incidents that have an impact and resonance on the Iraqi people. It addresses several areas, including political, economic, social and cultural issues. However, the social situation in Baghdad at the end of the economic crisis affected the lives of the working class, represented by the increase in electricity wages by the British Enlightenment Company. In view of this, the press in general and Al-Alam Al-Arabi newspaper in particular pushed to unite the efforts of associations and unions against the company, which resulted in a major strike with the support and contribution of café, restaurant, hotel and store owners and several influential political figures, which encouraged them to continue the boycott until 1934 and end the boycott. Officially by the Iraqi government.